Phase field modelling of ductile fracture in the frameworks of non-conventional thermodynamics and continuum damage mechanics. (1st February 2023) - Tsakmakis, Aris; Vormwald, Michael
Abstract: In the present work, a phase field approach for ductile fracture and fatigue failure in the framework of non-conventional thermodynamics is proposed. In contrast to brittle fracture, the physical mechanisms for fracture are supposed to be initiation, growth and coalescence of voids, driven by plastic deformation. Thus, the aim of the paper is to demonstrate how well-established ingredients of plasticity, continuum damage mechanics and phase field theories can be fit in the adopted framework. The main features of the proposed theory are that damage evolution is coupled to the evolution of plastic strain, that the appropriate modelling of yield stress effects in the free energy function is of central importance and that fatigue failure can be captured without employing fatigue degradation functions. Various numerical examples and comparisons with experimental data demonstrate the capabilities of the model.